Competências e necessidades de formação para o atendimento de crianças, adolescentes e suas famílias em situação de abuso sexual: perspectivas de conselheiros tutelares. - Vicente, Aparecido Renan (Universidade Federal de São Carlos, 2024)
Child and adolescent sexual abuse remain a challenge to the health of children, adolescents and their families. Despite being legitimized and the first access in situations of rights violations, the Guardianship Council has weaknesses in terms of dealing with these situations. Objective: It is to understand the competencies and training needs of guardianship counselors for the care of children, adolescents and their families in situations of sexual abuse. Methods: This study was developed based on a scope review and a qualitative approach. The review followed the guidelines of the Joanna Briggs Institute, with the following guiding question: What educational technologies are used to support the care of sexual violence against children and adolescents? Eight electronic libraries and databases were searched in March and April 2023, namely: Brazilian Digital Library of Theses and Dissertations (BDTD); VHL - Latin American and Caribbean Literature in Health Sciences;PubMed; Cumulative Index to Nursing and Allied Health Literature (CINAHL); Embase Biomedical AnswersScopus; Web of Science; ProQuest Dissertations; and American Psychological Association (APA PsycInfo). Regarding the qualitative study, it was anchored in the Paradigm of Complexity. The participants were 25 guardianship counselors recruited from snowball sampling. Data collection was performed in February and March 2023, through focus groups and semi-structured interviews on virtual platforms. Data analysis was carried out through reflective thematic analysis. Results: Concerning the scoping review, 14 studies were included. The technologies used to support the care of sexual abuse against children and adolescents were mostly classes with traditional methodologies, based on the discussion of concepts, consequences, identification and referrals in the face of this episode. In the qualitative study, three final themes appeared, namely: "Complexity of sexual abuse against children and adolescents"; "The performance of the Guardianship Council in the care of children, adolescents and their families in situations of sexual abuse"; and "Sexual abuse protection network involving children, adolescents and their families". Conclusions: The complexity necessary to understand and consequent care for sexual abuse was evidenced, especially because this violence happen in situations that involve and are interwoven with family, historical, cultural and social elements. To act in this context, there is a need to develop competencies that contemplate a polyocular vision, guided by humanization, welcoming, care coordination and comprehensiveness. The following implications were listed for the practice: (1) the development of skills for guardianship counselors who notice the multiplicity of elements present in the configuration of sexual abuse; (2) the permanent education of these professionals based on the realities experienced, covering topics such as humanization and welcoming, integrality of care, coordination of the care network; (3) the development of dialogued practices among the services present in the System for the Guarantee of the Children and Adolescents Rights to overcome reductionist conducts.
Skills and training needs for assisting children, adolescents and their families in situations of sexual abuse: perspectives from guardianship counselors.
Keywords: Abuso Sexual na Infância; Adolescente; Família; Capacitação profissional; Conselho tutelar; Childhood sexual abuse; Adolescent; Family; Professional training; Guardiaship council; CIENCIAS DA SAUDE